Composites and Structures for Regenerative Engineering. Issue 1621 (7th January 2014) - Laurencin, Cato T.; James, Roshan
ABSTRACT: Regenerative engineering was conceptualized by bridging the lessons learned in developmental biology and stem cell science with biomaterial constructs and engineering principles to ultimately generate de novo tissue. We seek to incorporate our understanding of natural tissue development to design tissue-inducing biomaterials, structures and composites than can stimulate the regeneration of complex tissues, organs, and organ systems through location-specific topographies and physico-chemical cues incorporated into a continuous phase. This combination of classical top-down tissue engineering approach with bottom-up strategies used in regenerative biology represents a new multidisciplinary paradigm. Advanced surface topographies and material scales are used to control cell fate and the consequent regenerative capacity. Musculoskeletal tissues are critical to the normal functioning of an individual and following damage or degeneration they show extremely limited endogenous regenerative capacity. The increasing demand for biologically compatible donor tissue and organ transplants far outstrips the availability leading to an acute shortage. We have developed several biomimetic structures using various biomaterial platforms to combine optimal mechanical properties, porosity, bioactivity, and functionality to effect repair and regeneration of hard tissues such as bone, and soft tissues such as ligament and tendon. Starting with simple structures, we have developed composite and multi-scale systems that very closely mimic the native tissue architecture and material composition. Ultimately, we aim to modulate the regenerative potential, including proliferation, phenotype maturation, matrix production, and apoptosis through cell-scaffold and host –scaffold interactions developing complex tissues and organ systems.